2011
DOI: 10.1189/jlb.0409233
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to tuberculosis is associated with TLR1 polymorphisms resulting in a lack of TLR1 cell surface expression

Abstract: Human TLR1 plays an important role in host defense against Mycobacterium tuberculosis. Our aim was to analyze the association of the loss of TLR1 surface expression and TLR1 SNPs with susceptibility to TB. TLR1neg and TLR1pos cells from healthy individuals were identified by flow cytometry and compared by sequencing. TLR1 expression was measured using quantitative real-time PCR and immunoblotting. TLR1 SNP analyses of healthy individuals and TB patients from EU-C and Ghana were performed, and association of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 52 publications
(87 reference statements)
4
62
0
1
Order By: Relevance
“…52 The simplifying explanation is that all of these polymorphisms are in strong LD with an uncharacterized regulatory variant. However, reduced TLR1 function decreases the risk of sepsis, 19,20 leprosy, 21,22,25,26,28 tuberculosis, 13,27 and other diseases. 18,31,50 Thus, variants that disrupt the function of TLR1 may be beneficial to the survival of the organism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…52 The simplifying explanation is that all of these polymorphisms are in strong LD with an uncharacterized regulatory variant. However, reduced TLR1 function decreases the risk of sepsis, 19,20 leprosy, 21,22,25,26,28 tuberculosis, 13,27 and other diseases. 18,31,50 Thus, variants that disrupt the function of TLR1 may be beneficial to the survival of the organism.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] TLR1, when in a heterodimer with TLR2, recognizes a variety of triacylated lipoproteins, 11 as well as other lipoproteins, and specific recognition targets include M. leprae, M. tuberculosis, Borrelia species, and a variety of fungal pathogens. 10,[12][13][14][15][16][17][18] Activation of the TLR1-TLR2 heterodimer is not always beneficial to the organism, as multiple studies have found that derived alleles at some SNPs inhibit TLR1 activity and reduce the risk of sepsis, leprosy, prostate cancer, pelvic inflammatory disease, and tuberculosis. [19][20][21][22][23][24][25][26][27] The foremost of these is rs5743618, whose derived allele c.2079T4G (p.(Ile602Ser)) reduces surface trafficking of the TLR1-TLR2 heterodimer, 28 resulting in a reduced response to heterodimer antagonists and, in turn, reduced activation of the NFkB pathway.…”
Section: Introductionmentioning
confidence: 99%
“…The other strong signals identified were either directly or indirectly related to diet, corresponding to genes encoding proteins involved in fatty acid metabolism, vitamin D levels, and celiac disease, or corresponded to genes involved in skin pigmentation [132]. Interestingly, the authors also detected strong selection signals in immunity-related genes, such as the TLR1–TLR6–TLR10 gene cluster, which is essential for the induction of inflammatory responses and is associated with susceptibility to infectious diseases [159, 160]. Thus, ancient DNA studies can help us to understand the mode of selection following changes in human lifestyle, and the extent to which such selective events increased the frequency of functional alleles associated with specific traits or disease conditions [131, 132, 161, 162].…”
Section: Favoring Advantageous Variants To Increase Adaptationmentioning
confidence: 99%
“…Present literature indicates that the outcome of Mtb infection is affected not only by virulence of the infecting strain of M. tuberculosis [17], but also by host environment, disease co-morbidities, and the genetic composition of the host, specifically the presence or absence of genes that regulate the immune system [14, 16, 1820]. Following Mtb infection, approximately 10 % of individuals will develop active TB (ATB) during their lifetime, while the majority of individuals will exhibit latent TB infection (LTBI) [21, 22].…”
Section: Introductionmentioning
confidence: 99%